Toward Exotic Layered Materials: 2D Cuprous Iodide. Issue 9 (19th January 2022) - Mustonen, Kimmo; Hofer, Christoph; Kotrusz, Peter; Markevich, Alexander; Hulman, Martin; Mangler, Clemens; Susi, Toma; Pennycook, Timothy J.; Hricovini, Karol; Richter, Christine; Meyer, Jannik C.; Kotakoski, Jani; et al.
Abstract: Heterostructures composed of 2D materials are already opening many new possibilities in such fields of technology as electronics and magnonics, but far more could be achieved if the number and diversity of 2D materials were increased. So far, only a few dozen 2D crystals have been extracted from materials that exhibit a layered phase in ambient conditions, omitting entirely the large number of layered materials that may exist at other temperatures and pressures. This work demonstrates how such structures can be stabilized in 2D van der Waals (vdw) stacks under room temperature via growing them directly in graphene encapsulation by using graphene oxide as the template material. Specifically, an ambient stable 2D structure of copper and iodine, a material that normally only occurs in layered form at elevated temperatures between 645 and 675 K, is produced. The results establish a simple route to the production of more exotic phases of materials that would otherwise be difficult or impossible to stabilize for experiments in ambient. Abstract : Only a few dozen 2D crystals have been successfully prepared, though many more—including metal iodides—are predicted to exist. A major reason for this disparity is their instability under ambient conditions. A wet‐chemical method to synthesize 2D‐CuI, stabilizing it by graphene encapsulation in a one‐step process, is designed, and its chemical structure is imaged.